PENGARUH PENGGUNAAN ARTIFICIAL INTELEGENCE (CHATGPT) TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Rahman Hakim, Arif; Arifudin, Iis; Ristiyani, Novi; Muliana, Wita; Sukriyah; Sartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and analyze the effect of using Artificial Intelligence (ChatGPT) on the critical thinking skills of students in the Distance Learning Islamic Education (PJJ PAI) Program at Universitas Islam Negeri Siber Syekh Nurjati Cirebon. The rapid adoption of AI has raised concerns regarding the potential degradation of intellectual independence due to instant information retrieval. This quantitative correlational study involved 100 active students selected through purposive sampling. Data were collected using an online Likert-scale questionnaire and analyzed using simple linear regression. The results showed that the majority of students exhibited a high intensity of ChatGPT usage while maintaining good critical thinking skills. There is a positive and significant effect of ChatGPT usage on students' critical thinking skills, with a significance value of 0.000 < 0.05. The coefficient of determination of 0.222 indicates that ChatGPT contributes 22.2% to stimulating critical thinking. In conclusion, ChatGPT does not automatically erode students' reasoning abilities; rather, it can stimulate critical thinking when used as an interactive discussion partner. The practical implications of these findings urge higher education institutions to formulate ethical guidelines for AI utilization and encourage educators to adopt Problem-Based Learning methods to prevent the misuse of AI technology.